The Self-experience of the Self - Gamba, Ezio (Religija ir kultūra, 2013)
Charles Larmore sums up in three statements the traditional position of philosophy about the self (with particular reference to René Descartes and John Locke): 1) it is impossible to be a self without being in relation with itself; 2) the relation that the self has with itself (and by which it is a self ) is a cognitive relation, it is a self-knowledge; 3) this relation of self-knowledge is of the same kind as the cognitive relation that the self has with the objects of the world. Larmore criticizes statements 2 and 3 and maintains that the relation (of the self with itself ) in which the nature of the self consists is not cognitive, but practical and normative: the nature of the self is the same relation of commitment that exists between my beliefs and my actions; each of my beliefs commits me to behave a certain way. In this paper, I want to refute Larmore’s criticism of statement 2 and to show, following Michel Henry, that the relation in which the nature of the self consists is actually a self-experience; I maintain that we can affirm statement 2 of the traditional position about the self without being forced to affirm also statement 3.
Keywords: the self; self-knowledge; self-experience; Charles Larmore